2020
DOI: 10.31234/osf.io/dpqrx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coffee or Tea? Examining Cross-Cultural Differences in Personality Nuances Across Former Colonies of the British Empire

Abstract: Cross-cultural comparisons often focus on differences in broad personality traits across countries. However, many cross-cultural studies report differential item functioning which suggests that considerable group differences are not accounted for by the overarching personality factors. We argue that this may reflect cross-cultural personality differences at a lower level of personality, namely personality nuances. To investigate the degree of cultural similarities and differences between participants of ten co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…But as was discussed before, items often have retest reliabilities of .65 or higher (Lowman, Wood, Armstrong, Harms, & Watson, 2018;Wood, Nye, & Saucier, 2010;Henry & Mõttus, 2020), which may be higher than many intuitively expect. Higher-than-assumed single item reliability is also consistent with findings that items out-predict scales for outcomes and other variables (Achaa-Amankwaa, Olaru, & Schroeders, 2020;Elleman, McDougald, Condon, & Revelle, 2020;Mõttus & Rozgonjuk, 2019;Seeboth & Mõttus, 2018;Vainik, Mõttus, Allik, Esko, & Realo, 2015). Therefore, the allegedly low reliability of items should not be a reason for not reporting item-level findings.…”
Section: Better Use Of Already Existing Datasupporting
confidence: 76%
See 1 more Smart Citation
“…But as was discussed before, items often have retest reliabilities of .65 or higher (Lowman, Wood, Armstrong, Harms, & Watson, 2018;Wood, Nye, & Saucier, 2010;Henry & Mõttus, 2020), which may be higher than many intuitively expect. Higher-than-assumed single item reliability is also consistent with findings that items out-predict scales for outcomes and other variables (Achaa-Amankwaa, Olaru, & Schroeders, 2020;Elleman, McDougald, Condon, & Revelle, 2020;Mõttus & Rozgonjuk, 2019;Seeboth & Mõttus, 2018;Vainik, Mõttus, Allik, Esko, & Realo, 2015). Therefore, the allegedly low reliability of items should not be a reason for not reporting item-level findings.…”
Section: Better Use Of Already Existing Datasupporting
confidence: 76%
“…Such examples abound (Mõttus et al, 2015); for example, Mõttus and Rozgonjuk (2019) reported that items within half of the personality facets varied in the directions of their age differences, leading items to contain over 40% more age-sensitive information than facets and over twice as much as the Big Five domains. More nuanced investigations into how personality is linked with various life outcomes or vary across cultures have led to similar conclusions (Achaa-Amankwaa, Olaru, & Schroeders, 2020;Elleman, McDougald, Condon, & Revelle, 2020;Seeboth & Mõttus, 2018;.…”
Section: What Makes Good Descriptive Research?mentioning
confidence: 88%
“…Such examples abound (Mõttus et al, 2015); for example, Mõttus and Rozgonjuk (2019) reported that items within half of the personality facets varied in the directions of their age differences, leading items to contain over 40% more age-sensitive information than facets and over twice as much as the Big Five domains. More nuanced investigations into how personality is linked with various life outcomes or vary across cultures have led to similar conclusions (Achaa-Amankwaa, Olaru, & Schroeders, 2020;Elleman et al, 2020;Seeboth & Mõttus, 2018;. At which level of a personality hierarchy should descriptive findings stop?…”
Section: What Makes Good Descriptive Research?mentioning
confidence: 90%
“…Patterns in how personality differences relate to the variables of interest can also be explored atheoretically. For example, item-or facet-level associations can be organized in the descending order of effect size to highlight the strongest associations and find commonalities in them (e.g., Achaa-Amankwaa et al, 2020;Elleman et al, 2020;Bem & Funder, 1978;Block, Block, & Gjerde, 1986;Block, Gjerde, & Block, 1991). In some fields such as genetics, recent progress has almost entirely resulted from atheoretically scanning association patterns rather than imposing theoretical constraints on the findings (e.g., Nagel et al, 2018;Plomin & von Stumm, 2018) and there is no reason why following suit could not help personality scientists.…”
Section: What Makes Good Descriptive Research?mentioning
confidence: 99%
“…Another study found that, across 40 outcomes, the specific variance of nuances accounted for a substantial portion of the predictive power of domain-level models, suggesting that the idiosyncrasies of individual items are more responsible for domain-level relationships than is commonly understood (Seeboth & Mõttus, 2018). Lastly, one recent study found that a participant's country of origin was better predicted with personality items than facets or domains (Achaa-Amankwaa, Olaru, & Schroeders, 2020). Taken together, this body of research indicates that examining personality-outcome relationships at a level higher than nuances "entails a substantial loss of information" (Mõttus et al, 2015, p. 25) and risks misattributing nuance-level personality-outcome relationships to broader traits.…”
Section: Us Zip Codes May Better Aggregate Personality Than Statesmentioning
confidence: 99%